Immunohistochemical Study of Nerve Growth Factor Expression in Hansen’s Disease - Fatma Lubna; Aijaz Abbas; Mohammad Adil; Kafil Akhtar (Indian Journal of Dermatopathology and Diagnostic Dermatology)
Aim: To study the immunoexpression of nerve growth factor (NGF) in Hansen’s disease to assess the diagnostic and prognostic significance. Objective: NGF is a neurotrophin and an important growth factor for the tissue remodeling process. Higher expression of NGF is observed in the lepromatous forms when compared to tuberculoid forms. Materials and Methods: The present prospective study was carried out in the Departments of Pathology and Dermatology at Aligarh Muslim University, Aligarh, Uttar Pradesh, India, in 50 patients of Hansen’s disease. Results: The study included 50 cases of Hansen’s disease. The majority of the cases were of borderline lepromatous, 15 (30.0%), followed by 12 (24.0%) cases each of borderline tuberculoid and tuberculoid leprosy. Higher staining intensity of NGF and a higher percentage of positive cells were observed in lepromatous leprosy (LL) cases as compared to tuberculoid leprosy (TT) cases. The highest number of cases with a high immunoreactivity score (IRS) was of LL, whereas TT cases showed a low IRS. Conclusion: The immunoexpression of NGF was more intense on the lepromatous side of the spectrum compared to the tuberculoid side, indicating the severity of the disease with less potential for cure.